Code-Switching in Digital Discourse: A Case Study of the Beropini Podcast by Gita Savitri Devi - Hapsa, Siti; Syarif, Andi Rachmawati; Faridawati, Faridawati (Journal of English Language and Education, 2025)
In bilingual societies, code-switching is a common linguistic practice that reflects both social identity and communicative style. Although numerous studies have examined code-switching in Indonesian podcasts, most have centered on domestic contexts, leaving limited attention to speakers living abroad. This study investigates code-switching in Beropini, a podcast by Gita Savitri Devi, to identify the dominant type of code-switching based on Poplack’s (2004) classification and to analyze its causal factors using Hoffmann’s (1991) framework. Employing a descriptive qualitative method through transcription, categorization, and researcher triangulation, the study identified 167 instances of code-switching: 163 intra-sentential, 3 tag-switching, and 1 inter-sentential. The main factors included expressing group identity (71 instances), talking about a particular topic (61), and repetition is used for emphasis (54), while other factors appeared less frequently. These findings demonstrate that code-switching in Beropini serves not only as a communicative strategy but also as a deliberate means of constructing bilingual identity within transnational digital discourse.